Systematic review and meta-analysis on outcome differences among patients with TICI2b versus TICI3 reperfusions: success revisited. Issue 9 (8th March 2018) - Kaesmacher, Johannes; Dobrocky, Tomas; Heldner, Mirjam R; Bellwald, Sebastian; Mosimann, Pascal J; Mordasini, Pasquale; Bigi, Sandra; Arnold, Marcel; Gralla, Jan; Fischer, Urs
Abstract : Objective: A reperfusion quality of thrombolysis in cerebral infarction (TICI)≥2b has been set as the therapeutic angiography target for interventions in patients with acute ischaemic stroke. This study addresses whether the distinction between TICI2b and TICI3 reperfusions shows a clinically relevant difference on functional outcome. Methods: A systematic literature review and meta-analysis was carried out and presented in conformity with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria to test the primary hypothesis that TICI2b and TICI3 reperfusions are associated with different rates of modified Rankin Scale (mRS) ≤2 at day 90. Secondary endpoints included rates of haemorrhagic transformations, mortality and excellent functional outcome (mRS ≤1). Summary estimates of ORs (sOR) with 95% CI were calculated using the inverse variance heterogeneity model accounting for multiple true effect sizes. Results: Fourteen studies on 2379 successfully reperfused patients were included (1131 TICI3, 1248 TICI2b). TICI3 reperfusions were associated with higher rates of functional independence (1.74, 95% CI 1.44 to 2.10) and excellent functional outcomes (2.01, 95% CI 1.60 to 2.53), also after including adjusted estimates. The safety profile of patients with TICI3 was superior, as demonstrated by lower rates of mortality (sOR 0.59, 95% CI 0.37 to 0.92) and symptomatic intracranial haemorrhages (sOR 0.42, 95% CI 0.25 to 0.71). Conclusion: TICI3 reperfusions are associated with superior outcome and better safety profiles than TICI2b reperfusions. This effect seems to be independent of time and collaterals. As reperfusion quality is the most important modifiable predictor of patients' outcome, a more conservative definition of successful therapy and further evaluation of treatment approaches geared towards achieving TICI3 reperfusions are desirable.